Tropical endomyocardial fibrosis: an overview - Verma, Vijay Kumar; Zafar, Khwaja Saifullah (International Journal of Research in Medical Sciences, 2017)
Tropical endomyocardial fibrosis is the commonest form of endemic restrictive cardiomyopathy that affects mainly children and adolescents, and is geographically restricted to some poor areas in the tropical and subtropical regions of the world such as Africa, Latin America and Asia including southern districts of India especially in the coastal belt of Kerala state. Sub-endocardial fibrosis affecting the apices and the inflow tracts of the right or left ventricle, or both; and varying degree of atrioventricular valve regurgitation defines the disease. Chronic systemic venous hypertension and severe pulmonary hypertension are characteristic features of right ventricular and Left ventricular endomyocardial fibrosis respectively. Due to lack of resources for research in the disease endemic areas, the exact epidemiology, etiology and pathogenesis remain unknown, and the natural history is incompletely understood. Various infections and toxic factors were postulated regarding its etiology. During the last few years, incidence of the disease has decreased considerably because of the significant improvement in the living standards of the people with the corresponding decline in the childhood malnutrition, infections, worm infestations and associated eosinophilia. It is a condition with high morbidity and mortality, for which no effective therapy is available. However, surgical management improves the natural history of this disease to some extent. We have conducted a systematic review of the most intriguing aspects of epidemiology, natural history, clinical picture and management of endomyocardial fibrosis, proposing new ways to increase research into this challenging and neglected cardiovascular disease. We relied primarily on articles in the MEDLINE database with either ‘‘endomyocardial fibrosis’’ or ‘‘endomyocardial sclerosis’’ in the title.